Last-Mile Delivery Models in E-Commerce: Impacts of Sectors, and Population Densities - Malmsten, Livia; Sundell, Sigrid (My University, 2025)
Last-mile logistics are often characterized by inefficiencies such as fragmented shipments and limited consolidation, all of which contribute to a growing number of businesses-to- consumer freight trips, increased congestion and greater environmental impact. Rising consumer demand for low-cost and fast deliveries, combined with growing sustainability concerns is heightening the pressure on delivery systems. This study explores how consumer preferences influence the structure of last-mile logistics solutions and aims to identify how these preferences can improve delivery efficiency. The study was conducted in the area of Gothenburg, Sweden, focusing on three distinct regions to examine variations in last-mile delivery options and consumer preferences. The primary preferences analyzed were time, cost, convenience, and environmental sustainability. Data was collected from 20 websites across various e-commerce sectors. The delivery methods evaluated included Home Delivery, Pick-Up Points, Parcel Lockers, and Click & Collect. Multiple data collection techniques were employed. The findings indicated that regional differences had no significant impact on the delivery options provided by the websites. However, the availability of delivery methods varied depending on the e-commerce sector. The findings indicate that increased transparency, such as clearer information on attendance, available time slots for home delivery, and environmental impact of delivery options could improve the efficiency and sustainability of last-mile logistics. The study is limited to Swedish e-commerce sectors, websites, and the area of Gothenburg.
Keywords: Last-Mile; Last-Mile Delivery; Consumer Preferences; E-commerce